Comparison between colposcopic and biopsy findings to determine the frequency cervical intraepithelial neoplasia I to III in visual inspection with acetic acid - Bhuiyan, Khaleda Akter; Das, Deepa; Sharmin, Mumu Tasnuva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: While visual inspection with acetic acid (VIA) is an effective and affordable screening tool, the determination of the severity of cervical intraepithelial neoplasia (CIN) relies heavily on the expertise of healthcare professionals and the interpretation of colposcopic and biopsy findings. The aim of this study is to compare the frequency CIN I-III in VIA positive cases with the help of colposcopic and biopsy findings. Methods: The prospective cross sectional descriptive study conducted among the VIA positive cases (n=100) who were attending at in colposcopic clinic of department of obstetrics and gynecology, Dhaka Bangabandhu Sheikh Mujib medical university (BSMMU) during 1st June 2010 to 30th August 2010. History includes present and past illness, personal, family history, drug history and blood pressure were done. Results: The mean duration of married life was 16.8±10.6 years and more than a half (52.0%) of the patients’ age was 15-20 years of their first intercourse. More than one fourth (27.0%) of the patients had irregular menstrual cycle and 10.0% patients were menopause. Most (72.0%) of the study patients were multipara and the mean age of 'last confinement was 7.8±6.8 years. Majority 38(38.0%) of the patient was normal, 25 (25.0%) of the study patients had CIN I and CIN II in 13 (13.0%), CIN III in 5 (5.0%), 4 (4.0%) had invasive carcinoma and 15 (15.0%) unsatisfactory colposcopy. The colposcopic related biopsy findings was observed, 27.1% of the study patients had CIN I, 12.9% had CIN II, 12.9% invasive carcinoma, 5.9% had CIN III and 5.9% had inflammatory change. Conclusions: CIN III in colposcopic-related biopsy findings was associated with a mixture of CIN I and CIN III in colposcopic examinations. Invasive carcinoma in biopsy results was linked to a combination of CIN III and invasive carcinoma in colposcopic findings.